The Effectiveness of Principal Supervision and Teacher Professional Competence on Teacher Performance in SMP Kisam Tinggi District, South OKU - Jauwiyah; Arafat, Yasir; Puspita, Yenny (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This research was made to obtain very accurate data which aims at the supervision of the principal and the professional competence of teachers which can independently or simultaneously with the performance of teachers in SMP Kisam Tinggi District, South OKU. This research used a quantitative method using product moment and multiple regressions. The population was 96 teachers in Kisam Tinggi District. Because the population is less than 100, the sample used is a sample population, which means that the entire population is sampled. The results of the research at each point in the formulation of the problem answered that there was a positive influence both individually or simultaneously as much as 31.4% and the remaining 68.6% which was seen from other factors.